IbOr Regulates Photosynthesis under Heat Stress by Stabilizing IbPsbP in Sweetpotato - Kang, Le; Kim, Ho S.; Kwon, Young S.; Ke, Qingbo; Ji, Chang Y.; Park, Sung-Chul; Lee, Haeng-Soon; Deng, Xiping; Kwak, Sang-Soo (Frontiers in Plant Science, 2017)
The Orange (Or) protein regulates carotenoid biosynthesis and environmental stress in plants. Previously, we reported that overexpression of the sweetpotato [Ipomoea batatas (L.) Lam] Or gene (IbOr) in transgenic Arabidopsis (referred to as IbOr-OX/At) increased the efficiency of photosystem II (PSII) and chlorophyll content after heat shock. However, little is known about the role of IbOr in PSII-mediated protection against abiotic stress. In this study, comparative proteomics revealed that expression of PsbP (an extrinsic subunit of PSII) is up-regulated in heat-treated IbOr-OX/At plants. We then identified and functionally characterized the PsbP-like gene (IbPsbP) from sweetpotato. IbPsbP is predominantly localized in chloroplast, and its transcripts are tissue-specifically expressed and up-regulated in response to abiotic stress. In addition, IbOr interacts with IbPsbP and protects it from heat-induced denaturation, consistent with the observation that transgenic sweetpotato overexpressing IbOr maintained higher PSII efficiency and chlorophyll content upon exposure to heat stress. These results indicate that IbOr can protect plants from environmental stress not only by controlling carotenoid biosynthesis but also by directly stabilizing PSII.